1981
DOI: 10.1093/nar/9.21.5811
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of zinc and copper within subnuclear nucleoprotein particles

Abstract: Nuclei from frozen calf thymus suspended in buffer were analyzed for metal content prior to and after repeated washing. After three such extractions about 0.1 micrograms Zn/mg DNA and 0.025 micrograms Cu/mg DNA remained tightly associated with chromatin. This level of metal was essentially unchanged with subsequent washings. Digestion of extracted nuclei with micrococcal nuclease yielded soluble nucleoprotein containing zinc and copper. Metal enriched regions of chromatin appeared to be preferentially solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Cu(II) is protein bound and is present in higher concentrations in the nucleus than in the cytosol (53). In the nucleus, copper exists in a nuclear histone protein complex located at the base of DNA loops, where it maintains the nuclear matrix and DNA folding (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Cu(II) is protein bound and is present in higher concentrations in the nucleus than in the cytosol (53). In the nucleus, copper exists in a nuclear histone protein complex located at the base of DNA loops, where it maintains the nuclear matrix and DNA folding (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Moreover, copper is an important structural metal ion in chromatin, [6][7][8] which contains about one copper ion per kilobase. [6] For these reasons, there is an increased interest in the ability of copper ion to participate in DNA-damaging reactions in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[6] For these reasons, there is an increased interest in the ability of copper ion to participate in DNA-damaging reactions in vivo. [8,9] Kinetic, [9][10][11] inhibitor, [4,5,9] and sequence-context [12][13][14][15] studies have all suggested that DNA damage induced by copper ion in the presence of H 2 O 2 occurs site-specifically at the sites of DNA-associated copper. However, the nature of the last DNA-oxidizing species produced by the interaction of the DNA-Cu I complex with H 2 O 2 remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…11) Copper exists in the cell nucleus at a relatively high concentration and closely associates with chromosomes and bases, 12,13) although its free ion form is absent in the body. 14) Thus, changes in DNA conformation could be involved in metal-mediated genotoxicity as well as oxidative damage but via different mechanism.…”
Section: Discussionmentioning
confidence: 99%